Pemodelan Kekuatan Gelombang di Pesisir Barat Kecamatan Kuta, Bali - Kenoly, Timothy; Hendrawan, I Gede; Dirgayusa, I Gusti Ngurah Putra (Journal of Marine Research and Technology; Vol 6 No 1 (2023): FEBRUARI 2023, 2023)
The coastal area is an important area with many different functions for both human and marine organisms.  Still, coastal regions are vulnerable to changes caused by various things, including waves. Waves can cause shoreline changes and erode coastal regions. Kuta District is one of the coastal areas on the island of Bali that are threatened with constant sediment erosion every year. One way to increase understanding of the wave and its effect on the coastal areas is through numerical modeling. This study aimed to determine the pattern of wave and wave strength distribution on the west coast of the Kuta district. The Finite Volume Coastal Ocean Model and SWAVE (FVCOM-SWAVE) coupling model that was used in this study utilized the Finite Volume method of computation with the unstructured triangular grid. The results showed that in West Season (December-January-February), the range of mean significant wave heights on the west coast of Kuta District is 0.05 - 0.2 m, and the wave power ranged from 1 to 30 W/m with the most considerable value of significant wave heights and wave power were encountered in January. Water areas near land have greater wave heights and wave power than areas far from land, except around Ngurah Rai International Airport. The movement of waves primarily comes from the southwest, the Bali Strait, to the east and is divided by the runway into following the northern and southern parts of the coast.  Thus, the most significant wave height ??and wave power values are found in the waters near Kuta beach and Legian beach .